Tata Cara Pelaporan SPT Tahunan Menggunakan e-Form: Studi Kasus: Guru-Guru Di Kecamatan Talamau Kabupaten Pasaman Barat - Rahmatullah Pratama; Dike Rama Putra; Widia Firta (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The teachers have increased knowledge and understanding of the procedures for reporting the Annual SPT using the e-Form. Teachers who take part in this activity can understand and apply the knowledge they get in filling out the Annual SPT using the e-Form. With the high enthusiasm they show, it is hoped that in the future they will also implement and carry out regular and disciplined annual SPT reporting.